Induction chemoimmunotherapy may improve outcomes of chemoradiotherapy in patients with unresectable stage III NSCLC - Guan, Song; Zhang, Shufeng; Ren, Kai; Li, Xingyue; Li, Xue; Zhao, Lujun (Frontiers in Immunology, 2023)
Background: Currently, the value of induction chemoimmunotherapy before chemoradiotherapy (CRT) in unresectable stage III non-small cell lung cancer (NSCLC) has not been explored. This study was designed to explore the efficacy and safety of induction chemoimmunotherapy in patients with unresectable stage III NSCLC. Methods: Unresectable stage III NSCLC patients who received CRT with or without induction chemoimmunotherapy between August 2014 and December 2021 were retrospectively enrolled. Progression-free survival (PFS) and overall survival (OS) were assessed from the initiation of treatment and estimated by the Kaplan‒Meier method. The potential factors affecting PFS and OS were analyzed by univariate and multivariate Cox regression models. One-to-one propensity score matching (PSM) was used to further minimize confounding. Results: A total of 279 consecutive patients were enrolled, with 53 (19.0%) receiving induction chemoimmunotherapy followed by CRT (I-CRT group), and the remaining 226 (81.0%) receiving CRT alone (CRT group). After PSM, the median PFS was 24.8 months in the I-CRT group vs. 13.3 months in the CRT group (P=0.035). The median OS was not reached (NR) vs. 36.6 months ((P=0.142). The incidence of treatment-related adverse events (TRAEs) was similar in both groups, except that the incidence of hematological toxicity was higher in the I-CRT group (77.1% vs. 58.3%, P=0.049). Compared to induction chemotherapy, induction chemoimmunotherapy demonstrated a superior objective response rate (60.4% vs. 22.2%, P<0.001) and further prolonged PFS (median NR vs. 13.2 months, P=0.009) and OS (median NR vs. 25.9 months, P=0.106) without increasing the incidence of TRAEs in patients receiving concurrent chemoradiotherapy. Conclusion: Induction chemoimmunotherapy is safe and may improve outcomes of CRT in patients with unresectable stage III NSCLC. Moreover, induction chemoimmunotherapy may further improve treatment response and survival outcomes compared to induction chemotherapy before cCRT.